Total synthesis of the novel benzophenone NP-011694. Issue 33 (12th August 2015) - Noncovich, Alain; Ung, Jane; Patron, Andrew
Graphical abstract: Abstract: We report the total synthesis of NP-011694, a previously unreported fungal fermentation product from Analyticon Gmbh. The convergent synthesis employs Turbo Grignard and lithiation strategies, along with novel conditions for the simultaneous removal of multiple phenolic MOM groups.